KUNASHIR (KURILES) OAK 400-YEAR RECONSTRUCTION OF TEMPERATURE AND RELATION TO THE PACIFIC DECADAL OSCILLATION - Jacoby G.; Frank D.; D'Arrigo R.; Solomina O.; Eremenko N. (My University, 2004)
Paleoclimatic records of northwest Pacific variations are scarce but can be extended by proxy records from old-aged trees around the North Pacific Rim. In July of 2001 on Kunashir Island at the southern extent of the Kuriles, tree cores were extracted from century-old oaks (Quercus crispula) and developed into a 400-year tree-ring width index series. Analyses showed the ring-width indices to correlate strongly with summer (June–September) temperatures as recorded at Ugno-Kurilsky on the Island. The summer temperatures were reconstructed using the tree-ring data and 52% of the variance was explained by the tree-ring indices. The recorded temperature data and the tree-ring data show similar correlation patterns with sea-surface temperatures (SSTs) of the North Pacific. Studies of North Pacific variations, as quantified by the Pacific Decadal Oscillation (PDO), show the PDO to be an important index of large-scale climate variation. The tree-ring series explains more than 33% of the variance of the July–September Pacific Decadal Oscillation and has similar spectral properties, further supporting the concept of multidecadal variation or shifts in North Pacific climate, for four centuries.
Keywords: Paleoclimate; Tree rings; North Pacific; PDO